Monetary and Macroprudential Policies to Manage Capital Flows - Medina Guzman, Juan Pablo; Roldos, Jorge (Washington, D.C. : International Monetary Fund, 2014)
We study interactions between monetary and macroprudential policies in a model with nominal and financial frictions. The latter derive from a financial sector that provides credit and liquidity services that lead to a financial accelerator-cum-fire-sales amplification mechanism. In response to fluctuations in world interest rates, inflation targeting dominates standard Taylor rules, but leads to increased volatility in credit and asset prices. The use of a countercyclical macroprudential instrument in addition to the policy rate improves welfare and has important implications for the conduct of monetary policy. 'Leaning against the wind' or augmenting a standard Taylor rule with an argument on credit growth may not be an effective policy response.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet